Frequency and Management of Respiratory Emergencies - Muhammad Abas Khan; Bushra Arif; Muhammad Usman Sharif; Hameed, Abdul; Naveed Ahmed; Nithasha Khan; Muhammad Usman Khan (Journal of Health, Wellness and Community Research, 2025)
Background: Respiratory emergencies are among the most frequent causes of acute presentations in emergency departments worldwide and are associated with significant morbidity and mortality. Exacerbations of chronic airway diseases such as chronic obstructive pulmonary disease (COPD) and asthma, as well as acute respiratory infections and pulmonary edema, account for a substantial proportion of emergency visits. Early recognition and evidence-based management are essential to prevent deterioration and reduce the need for advanced respiratory support. Objective: To assess the frequency, clinical characteristics, and management strategies of respiratory emergencies presenting to the emergency department of Lady Reading Hospital, Peshawar. Methods: A descriptive cross-sectional study was conducted in the emergency department from September to December 2024. A total of 422 patients presenting with respiratory emergencies were included through convenience sampling. Data on demographics, clinical diagnosis, management interventions, and outcomes were collected using a structured proforma and analyzed using SPSS version 23. Descriptive statistics were calculated, and associations between variables were assessed using chi-square tests with a significance level of p < 0.05. Results: Of the 422 patients included, 61.6% were male, and the majority were aged 21–40 years (30.8%). COPD exacerbations (32.0%) and asthma attacks (26.1%) were the most frequent diagnoses, followed by acute bronchitis (20.1%), pneumonia (14.2%), and pulmonary edema (7.6%). Oxygen therapy (75.8%) and nebulized bronchodilators (66.4%) were the most common interventions, while systemic corticosteroids were administered in 49.8% of cases. Antibiotic therapy was required in 34.4% of patients, and mechanical ventilation was necessary in only 5.9%. Conclusion: Respiratory emergencies are predominantly caused by chronic airway disease exacerbations and acute respiratory infections. Early and evidence-based management with oxygen therapy, bronchodilators, and systemic corticosteroids plays a crucial role in preventing progression to respiratory failure. Strengthening emergency care protocols, improving outpatient disease management, and ensuring resource availability are essential for optimizing patient outcomes